2004
DOI: 10.1016/s0140-6736(04)17018-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potentially modifiable risk factors associated with myocardial infarction in 52 countries (the INTERHEART study): case-control study

Abstract: Abnormal lipids, smoking, hypertension, diabetes, abdominal obesity, psychosocial factors, consumption of fruits, vegetables, and alcohol, and regular physical activity account for most of the risk of myocardial infarction worldwide in both sexes and at all ages in all regions. This finding suggests that approaches to prevention can be based on similar principles worldwide and have the potential to prevent most premature cases of myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

201
4,180
33
219

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9,767 publications
(4,887 citation statements)
references
References 35 publications
201
4,180
33
219
Order By: Relevance
“…In the present study, higher apoB/apoA‐I ratio was associated with faster AS progression independently of the level of LDL‐C, which did not reach significance level. In patients with coronary artery disease, several studies reported that apoB/apoA‐I ratio is a powerful predictor of adverse events and is superior to conventional lipid parameters, especially in patients with LDL‐C within normal ranges 29, 49, 50. In our study, the level of LDL‐C was within normal limits in the vast majority of patients, and apoB/apoA‐I ratio outweighed LDL‐C to predict disease progression in this series.…”
Section: Discussionsupporting
confidence: 47%
“…In the present study, higher apoB/apoA‐I ratio was associated with faster AS progression independently of the level of LDL‐C, which did not reach significance level. In patients with coronary artery disease, several studies reported that apoB/apoA‐I ratio is a powerful predictor of adverse events and is superior to conventional lipid parameters, especially in patients with LDL‐C within normal ranges 29, 49, 50. In our study, the level of LDL‐C was within normal limits in the vast majority of patients, and apoB/apoA‐I ratio outweighed LDL‐C to predict disease progression in this series.…”
Section: Discussionsupporting
confidence: 47%
“…In this population of Hispanic/Latino adults living in Costa Rica, we found that poor predictive lifestyle behaviors were associated with higher odds of MI, in line with previous studies 7, 9, 11, 36, 37, 38. The association for the GRS and higher odds of MI was consistent with previous literature analyzing SNPs in the chromosome 9p21 and higher risk of CHD and mortality 6, 10, 12.…”
Section: Discussionsupporting
confidence: 92%
“…A similar gradient of population‐attributable risk of only lifestyle factors was shown in a case–control study (15 152 cases and 14 820 controls) of acute MI in 52 countries, where the strongest risk factors for MI were smoking (population‐attributable risk=36%), abdominal obesity (20.1%), daily fruit and vegetables (13.7%), physical activity (12.2%), and regular alcohol consumption (7.1%) 37. In line with these results, strong evidence support that the modification of lifestyle factors could potentially decrease the risk of CHD, MI, stroke, and related clinical risk factors7, 9, 11, 36, 42, 43 even in secondary prevention 38…”
Section: Discussionsupporting
confidence: 71%
“…Other reported modifiable risk factors32 including psychosocial factors, nutrition, and alcohol use were not assessed in this study.…”
Section: Methodsmentioning
confidence: 99%